2022
DOI: 10.2337/figshare.17282138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence of Type 1 Diabetes in Children and Adolescents During the COVID-19 Pandemic in Germany: Results From the DPV Registry

Abstract: Objective: The aim of this study was to investigate the incidence of type 1 diabetes in children and adolescents during the Covid-19 pandemic in Germany compared to previous years. <br>Research Design and Methods: Based on data from the multicenter German Diabetes Prospective Follow-up Registry (DPV), we analyzed the incidence of type 1 diabetes per 100,000 patient years in children and adolescents from January 1, 2020, through June 30, 2021. Using Poisson regression models, expected incidences for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
0
19
1
Order By: Relevance
“…In contrast, the proposition of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection as a trigger for new-onset diabetes has to contend with seemingly conflicting evidence regarding increased diabetes incidence rates during the COVID-19 pandemic as well as the considerable difficulties to distinguish an infectious diabetes origin from a multiplicity of pandemicrelated but indirect potential causalities (Barrett et al, 2022;Drucker, 2021;Ibrahim et al, 2021;Kamrath et al, 2022;Khunti et al, 2021;Sathish et al, 2021). Although the aggregate epidemiological evidence ostensibly argues against a direct diabetogenic potential of SARS-CoV-2 infection, this assessment is certainly provisional in consideration of the manifold ramifications of pandemic containment measures, the evolving landscape of clinical studies, various diagnostic challenges (e.g., a precise clinical definition of diabetes, previously undiagnosed type 1 or 2 diabetes [T1D or T2D, respectively]), the different pathophysiological mechanisms promoting acute and/ or prolonged glycometabolic perturbations (including hyperglycemia and insulin resistance typically associated with critical illness), and the possibility that a history of SARS-CoV-2 infection may alter diabetes incidence rates in the future (Al-Aly et al, 2021;Clarke et al, 2021;Drucker, 2021;Ibrahim et al, 2021;Jivanji et al, 2017;Kamrath et al, 2022;Li et al, 2020a;Misra et al, 2021;Montefusco et al, 2021;Reiterer et al, 2021). However, in the current context, a balanced evaluation of the available evidence also has to inform and delimit any speculation about the precise relevance of ex vivo and in vitro studies seeking to elucidate the potential for b cell infection, incapacitation, and/or destruction by SARS-CoV-2 (Accili, 2021;Atkinson and Powers, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the proposition of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection as a trigger for new-onset diabetes has to contend with seemingly conflicting evidence regarding increased diabetes incidence rates during the COVID-19 pandemic as well as the considerable difficulties to distinguish an infectious diabetes origin from a multiplicity of pandemicrelated but indirect potential causalities (Barrett et al, 2022;Drucker, 2021;Ibrahim et al, 2021;Kamrath et al, 2022;Khunti et al, 2021;Sathish et al, 2021). Although the aggregate epidemiological evidence ostensibly argues against a direct diabetogenic potential of SARS-CoV-2 infection, this assessment is certainly provisional in consideration of the manifold ramifications of pandemic containment measures, the evolving landscape of clinical studies, various diagnostic challenges (e.g., a precise clinical definition of diabetes, previously undiagnosed type 1 or 2 diabetes [T1D or T2D, respectively]), the different pathophysiological mechanisms promoting acute and/ or prolonged glycometabolic perturbations (including hyperglycemia and insulin resistance typically associated with critical illness), and the possibility that a history of SARS-CoV-2 infection may alter diabetes incidence rates in the future (Al-Aly et al, 2021;Clarke et al, 2021;Drucker, 2021;Ibrahim et al, 2021;Jivanji et al, 2017;Kamrath et al, 2022;Li et al, 2020a;Misra et al, 2021;Montefusco et al, 2021;Reiterer et al, 2021). However, in the current context, a balanced evaluation of the available evidence also has to inform and delimit any speculation about the precise relevance of ex vivo and in vitro studies seeking to elucidate the potential for b cell infection, incapacitation, and/or destruction by SARS-CoV-2 (Accili, 2021;Atkinson and Powers, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 It has been demonstrated that the incidence of type 1 diabetes in children increased only a few months after the Covid-19 waves. 11,12 With this background, it is important to note that we found an increased insulin requirement in children with onset of type 1 diabetes after the first wave of the Covid-19 pandemic. This may indicate more rapid autoimmune destruction of beta cells during the pandemic.…”
Section: Discussionmentioning
confidence: 84%
“…Only few formally explored trends originating from long-term run population based registers. 8,9 Recently, studies have been published that utilized big collections of electronic health records or medical claims, reporting conflicting results. [10][11][12] We therefore explored the data of Czech Childhood Diabetes Register, examining data ascertained over 2020-2021 when Czechia was very severely hit by several consecutive waves of COVID-19, and compared them to trends from the previous decade, also searching for patterns explainable by the dynamics of the pandemic, or by pandemic contingency measures.…”
mentioning
confidence: 99%